2008
DOI: 10.1016/j.ydbio.2008.03.002
|View full text |Cite
|
Sign up to set email alerts
|

Requirement of Oct3/4 function for germ cell specification

Abstract: In mammalian embryos, PGCs (primordial germ cells) are specified from a pluripotent epiblast cell population after implantation. In this study, we demonstrated an essential role for the germline-specific transcription factor Oct3/4 in PGC specification. We generated chimeric embryos with ZHBTc4 ES cells lacking both alleles of the Oct3/4 gene (pou5f1). Pluripotency was maintained by an Oct3/4 transgene, and its expression was suppressed by doxycycline (Dox). Transcription of the Oct3/4 transgene in the ES-deri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
48
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 55 publications
(53 citation statements)
references
References 38 publications
5
48
0
Order By: Relevance
“…In this work, we investigated the role of Sox2 during mouse gametogenesis. Our results reveal that Sox2 deletion during the establishment of germ cell lineage impairs PGC development, as previously shown for Prdm14 [16], Oct4 [17,18], and Nanog [19]. We also found that Sox2 is essential for PGC proliferation in vivo and in vitro, and that it affects the expression of genes which are critical for their development.…”
Section: Introductionsupporting
confidence: 88%
See 1 more Smart Citation
“…In this work, we investigated the role of Sox2 during mouse gametogenesis. Our results reveal that Sox2 deletion during the establishment of germ cell lineage impairs PGC development, as previously shown for Prdm14 [16], Oct4 [17,18], and Nanog [19]. We also found that Sox2 is essential for PGC proliferation in vivo and in vitro, and that it affects the expression of genes which are critical for their development.…”
Section: Introductionsupporting
confidence: 88%
“…Up-to-date few genes have been demonstrated to be essential for the establishment of the germ cell line: Blimp1 [12], Prdm14 [16], Oct4 [18] and AP2-c [57]. Our present data show for the first time that also Sox2, at least in mice, is required for PGC development, both during their specification period and during their proliferative phase which precedes their sexual differentiation, through the regulation of genes which control their proliferation, their cellular identity as well as their potential pluripotency.…”
Section: Resultsmentioning
confidence: 99%
“…There is evidence that Oct4 is essential for the emergence of Stella-positive PGCs (Table 1) (Okamura et al 2008). Conditional knockout of Oct4 or conditional knockdown of Nanog in migrating PGCs results in the death of PGCs by apoptosis, indicating the importance of these gene products in the maintenance of PGCs (Table 1) (Kehler et al 2004;Chambers et al 2007;Yamaguchi et al 2009).…”
Section: The Functions Of Pluripotency Genes In Pgcsmentioning
confidence: 99%
“…The precise mechanisms of the actions of these molecules in PGCs and the modes of their regulation by the key specification genes, such as Prdm1 and Prdm14, remain to be investigated. It will also be important to clarify the precise roles of key pluripotency genes such as Pou5f1, Sox2, and Nanog for PGC specification (Okamura et al 2008), although POU5F1 and NANOG have been shown to be critical to the survival of PGCs at relatively later stages, i.e. wE9.5 (Kehler et al 2004, Chambers et al 2007, Yamaguchi et al 2009).…”
Section: Key Regulators For Pgc Specificationmentioning
confidence: 99%